A case of mixed-pattern calcifications in multinodular goiter associated with a benign diagnosis. (2019) - Bianchi, D.; Morandi, U.; Stefani, A.; Aramini, B.
Highlights: Calcified nodules in a goiter are often found when performing an ultrasound of the neck. Analysis of different calcification patterns could contribute to discriminating between nodules. Mixed pattern calcifications is not so frequent and not interpreted. We believe that a better radiologic evaluation setting of thyroid nodules needs to be performed. Abstract: Background: Calcified nodules are often found in a goiter when performing an ultrasound of the neck. An analysis of different calcification patterns could contribute to discriminating between nodules with a lower malignancy risk and those with a higher malignancy risk. In certain cases, the results of a simple cytological analysis of a nodule are not specific enough to be completely trusted. Case presentation: We present the case of a goiter with a mixed calcification pattern, including a type of calcification that is strongly associated with a malignant diagnosis, for which a completely benign diagnosis was determined. Conclusion: We believe that further studies examining a combination of ultrasound (US) and computed tomography (CT) scan presentations of thyroid nodules need to be performed.